Los ayuntamientos y la cooperación para el desarrollo: el papel de los hermanamientos - Ruiz Seisdedos, Susana (Revista Española de Desarrollo y Cooperación, 2023)
In this article we aim at studying the specificities of one of the instrument of decentralized cooperation: the town-twinnings. The decentralized cooperation is fundamental to analyze the Spanish cooperation due to its qualitative and quantitative importance over the last years. From this perspective, the towntwinnings are shaped as an instrument which makes reality a horizontal cooperation. This offers real co-responsibility and North and South societies’ empowerment that redounds to increase the Third world communities’ quality of life.